Sodobna izhodišča redčenj - Diaci, Jurij (Gozdarski vestnik, 2021)
Various methods of thinning forest stands are common in Europe. These are partly a response to diverse management objectives, partly due to tradition and cultural context. With environmental changes, rapidly transforming socio-economic conditions, and a general decline in forest management, decisions about the optimal method and intensity of thinnings are becoming increasingly important. In this paper, we compare situational thinning, thinning of clusters and groups, thinning of variable density and selective thinning, traditional in Slovenia. We propose guidelines for combining various thinnings and choosing a suitable model and program of thinning. Based on the synthesis of previous research, we point out that field experiments are important for the evidence-based improvement of thinning methods.
Keywords: crop tree distribution; forest tending; gojenje gozdov; nega gozda; porazdelitev izbrancev; racionalizacija; rationalization; redčenje; silviculture; stabilnost sestoja; stand stability; thinning